Haemolytic effects of Samanea saman (Jacq.), Tectona grandis (L.) and Dipterocarpus turbinatus (Gaertn) seed extracts on Singhi fish, Heteropneustes fossilis (Bloch) - Nasiruddin, Munira; Azadi, Mohammad Ali; Chowdhury, Shabnam (Journal of the Asiatic Society of Bangladesh, Science, 2013)
The haemolytic effects of distilled water, 50% ethyl alcohol and 100% ethyl alcohol extracts of three plant seeds, Fulkoroi (Samanea saman), shegoon (Tectona grandis) and Gargan (Dipterocarpus turbinatus) were studied on a predatory fish Heteropneustes fossilis under laboratoary conditions. Comparative data of control and treated fishes showed that the toxic components induced changes in the blood parameters. Piscicides inducing toxicity were evident from decreased RBC counts, low haemoglobin percentage and decreased PCV, MCV, MCH values but increased WBC counts. Haemolysis included shrunken or swollen RBC, granulated nuclei of RBC and pyknotic and swollen nuclei of WBC, cellular damage resulting in bare nuclei of RBC and WBC, clumping of RBC and syncitium of RBC matrix. Damage of blood cells with 100% ethyl alcohol extract was pronounced with all the seed extracts. The order of toxicity on the blood parameters statistically were T. grandis > S. saman > D. turbinatus seed extracts. On the basis of haemolysis of blood cell the effects were D. turbinatus > S. saman > T. grandis seed extracts. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15323 J. Asiat. Soc. Bangladesh, Sci. 38(1): 83-91, June 2012